2020
DOI: 10.1016/j.jinf.2020.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The duration of infectiousness of individuals infected with SARS-CoV-2

Abstract: Objectives: To summarise the evidence on the duration of infectiousness of individuals in whom SARS-CoV-2 ribonucleic acid is detected. Methods: A rapid review was undertaken in PubMed, Europe PubMed Central and EMBASE from 1 January 2020 to 26 August 2020. Results: We identified 15 relevant studies, including 13 virus culture and 2 contact tracing studies. For 5 virus culture studies, the last day on which SARS-CoV-2 was isolated occurred within 10 days of symptom onset. For another 5 studies, SARS-CoV-2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 32 publications
6
123
1
1
Order By: Relevance
“…Prolonged detection of viral replication has been demonstrated in immunosuppressed patients 14 ; however, our results show that viral replication can also be detected in immunocompetent patients, even with moderate or low viral loads, for longer periods of time than those previously described. 7 , 12 , 15 It remains to be seen whether this finding is related to our higher cell culture positivity rate (51.6%) in patients with severe COVID-19 compared with that reported previously (9%), 7 due to technical factors such as cell line permissiveness to SARS-CoV-2. 16 Ideally, viral viability should be measured in human nasopharyngeal epithelium cell culture.…”
Section: Discussionmentioning
confidence: 54%
“…Prolonged detection of viral replication has been demonstrated in immunosuppressed patients 14 ; however, our results show that viral replication can also be detected in immunocompetent patients, even with moderate or low viral loads, for longer periods of time than those previously described. 7 , 12 , 15 It remains to be seen whether this finding is related to our higher cell culture positivity rate (51.6%) in patients with severe COVID-19 compared with that reported previously (9%), 7 due to technical factors such as cell line permissiveness to SARS-CoV-2. 16 Ideally, viral viability should be measured in human nasopharyngeal epithelium cell culture.…”
Section: Discussionmentioning
confidence: 54%
“…Walsh et al recently published a review in this journal focusing on the duration of infectiousness in SARS-CoV-2 infected individuals. ( 1 ) Based on available data from SARS-CoV-2 culture studies and contract tracing studies included in this review, the authors reported that patients with mild-to-moderate Coronavirus Disease 2019 (COVID-19) are considered to be without infectious potential beyond day 10 after the onset of symptoms. In contrast, immunocompromised and severe-to-critical patients may have prolonged viral shedding and, thus, may also provide prolonged infectiousness.…”
Section: Dear Editormentioning
confidence: 99%
“…Among those factors, our study and others highlight the importance of the RT-PCR method used ( Dust et al, November 2020 , Procop et al, October 5, 2020 , Kasteren et al, July 2020 , Zhen et al, April 27, 2020 ). The potential patient contagiousness, evaluated in the foreground on clinical criteria and time from symptoms onset, cannot be determined on the sole RT-PCR Ct result and can also be partly estimated after inoculation in cell culture ( Walsh et al, October 10, 2020 ). If PCR thresholds are given beyond which viral excretion can be estimated as low, they will remain strictly dependent on the technique used.…”
Section: Resultsmentioning
confidence: 99%